Time to include burden of surgical injuries after disasters in the Global Surgery agenda? An assessment of DALYs and averted burden by surgery after the 2008 Wenchuan earthquake. Issue 5 (1st October 2018) - Rodriguez-Llanes, Jose Manuel; Hellman, Lina; Wu, Qi; van den Oever, Barbara; Pan, Liang; Albela Miranda, Manuel; Chen, Gao; Zhang, De-Sheng; Guha-Sapir, Debarati; Von Schreeb, Johan
Abstract : Unlike other disasters, injury rates after earthquakes are still on the rise at a global scale. With an estimated one million people injured by earthquakes in the last decade, the burden of injury is considerable. Importantly, the surgical procedures carried out by healthcare facilities are capable to avert part of this burden. Yet both burdens remain unquantified using understandable metrics. We explored in this analysis a method to calculate them using disability-adjusted life years (DALYs), an internationally accepted measure expressing years of healthy life lost due to a health condition. We used data from a large standardised hospital database of earthquake-related injuries with complete information on International Classification of Diseases for injury and surgical procedures, sex and age information. DALYs and averted DALYs were calculated by injury types and per patient using disability weights available in the literature and expert opinion. We also suggested how DALYs might be further converted into an economic measure using approaches in the published literature. We estimated 10 397 DALYs as the earthquake surgical-injury burden produced in 1861 hospitalised patients treated in a single hospital (on average, 5.6 DALYs per patient). Our study also assessed that 4379 DALYs, or 2.4 DALYs per patient, were averted by surgery (42%). In economic terms, DALY losses amounted to US36.1 million, from which US15.2 million were averted by surgery in our case study. We urge to systematically estimate these impacts through improvements in the routine reporting of injury diagnoses and surgical procedures by health systems, potentially improving prevention policies and resource allocation to healthcare facilities.